Difference between revisions of "009B Sample Midterm 1, Problem 1"

From Math Wiki
Jump to navigation Jump to search
Line 1: Line 1:
 
<span class="exam">Evaluate the indefinite and definite integrals.
 
<span class="exam">Evaluate the indefinite and definite integrals.
  
::<span class="exam">a) <math>\int x^2\sqrt{1+x^3}~dx</math>
+
<span class="exam">(a) &nbsp; <math>\int x^2\sqrt{1+x^3}~dx</math>
::<span class="exam">b) <math>\int _{\frac{\pi}{4}}^{\frac{\pi}{2}} \frac{\cos(x)}{\sin^2(x)}~dx</math>
+
 
 +
<span class="exam">(b) &nbsp; <math>\int _{\frac{\pi}{4}}^{\frac{\pi}{2}} \frac{\cos(x)}{\sin^2(x)}~dx</math>
  
  
Line 8: Line 9:
 
!Foundations: &nbsp;  
 
!Foundations: &nbsp;  
 
|-
 
|-
| How would you integrate <math style="vertical-align: -12px">\int \frac{\ln x}{x}~dx?</math>
+
| How would you integrate &nbsp; <math style="vertical-align: -12px">\int \frac{\ln x}{x}~dx?</math>
 +
|-
 +
|
 +
&nbsp; &nbsp; &nbsp; &nbsp; You can use &nbsp;<math style="vertical-align: 0px">u</math>-substitution.
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp; Let &nbsp;<math style="vertical-align: -5px">u=\ln(x).</math>
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp; Then, &nbsp;<math style="vertical-align: -13px">du=\frac{1}{x}dx.</math>
 
|-
 
|-
 
|
 
|
::You could use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -5px">u=\ln(x).</math> Then, <math style="vertical-align: -13px">du=\frac{1}{x}dx.</math> Thus,
+
&nbsp; &nbsp; &nbsp; &nbsp; Thus,  
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\int \frac{\ln x}{x}~dx} & = & \displaystyle{\int u~du}\\
 
\displaystyle{\int \frac{\ln x}{x}~dx} & = & \displaystyle{\int u~du}\\
 
&&\\
 
&&\\
 
& = & \displaystyle{\frac{u^2}{2}+C}\\
 
& = & \displaystyle{\frac{u^2}{2}+C}\\
 
&&\\
 
&&\\
& = & \displaystyle{\frac{(\ln x)^2}{2}+C.}\\
+
& = & \displaystyle{\frac{(\ln x)^2}{2}+C.}
 
\end{array}</math>
 
\end{array}</math>
 
|}
 
|}
 +
 +
 
'''Solution:'''
 
'''Solution:'''
  
Line 28: Line 38:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|We need to use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: -2px">u=1+x^3.</math> Then, <math style="vertical-align: 0px">du=3x^2dx</math> and&thinsp; <math style="vertical-align: -13px">\frac{du}{3}=x^2dx.</math>
+
|We use &nbsp;<math style="vertical-align: 0px">u</math>-substitution.  
 
|-
 
|-
|Therefore, the integral becomes&thinsp;  
+
|Let &nbsp;<math style="vertical-align: -2px">u=1+x^3.</math>
 
|-
 
|-
|
+
|Then, &nbsp;<math style="vertical-align: 0px">du=3x^2dx</math>&nbsp; and &nbsp;<math style="vertical-align: -13px">\frac{du}{3}=x^2dx.</math>
::<math style="vertical-align: -13px">\frac{1}{3}\int \sqrt{u}~du.</math>
+
|-
 +
|Therefore, the integral becomes
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp; <math style="vertical-align: -13px">\frac{1}{3}\int \sqrt{u}~du.</math>
 
|}
 
|}
  
Line 39: Line 52:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|We now have:
+
|We now have
 
|-
 
|-
|
+
|&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
::<math>\begin{array}{rcl}
+
\displaystyle{\int x^2\sqrt{1+x^3}~dx} & = & \displaystyle{\frac{1}{3}\int \sqrt{u}~du}\\
\displaystyle{\int x^2\sqrt{1+x^3}~dx} & = & \displaystyle{\int x^2\sqrt{1+x^3}~dx}\\
 
&&\\
 
& = & \displaystyle{\frac{1}{3}\int \sqrt{u}~du}\\
 
 
&&\\
 
&&\\
 
& = & \displaystyle{\frac{2}{9}u^{\frac{3}{2}}+C}\\
 
& = & \displaystyle{\frac{2}{9}u^{\frac{3}{2}}+C}\\
 
&&\\
 
&&\\
& = & \displaystyle{\frac{2}{9}(1+x^3)^{\frac{3}{2}}+C.}\\
+
& = & \displaystyle{\frac{2}{9}(1+x^3)^{\frac{3}{2}}+C.}
 
\end{array}</math>
 
\end{array}</math>
 
|}
 
|}
Line 57: Line 67:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|Again, we need to use <math>u</math>-substitution. Let <math style="vertical-align: -5px">u=\sin(x).</math> Then, <math style="vertical-align: -5px">du=\cos(x)dx.</math> Also, we need to change the bounds of integration.
+
|We use &nbsp;<math>u</math>-substitution.  
 
|-
 
|-
|Plugging in our values into the equation <math style="vertical-align: -5px">u=\sin(x),</math> we get <math style="vertical-align: -15px">u_1=\sin\bigg(\frac{\pi}{4}\bigg)=\frac{\sqrt{2}}{2}</math> and <math style="vertical-align: -16px">u_2=\sin\bigg(\frac{\pi}{2}\bigg)=1.</math>
+
|Let &nbsp;<math style="vertical-align: -5px">u=\sin(x).</math>
 +
|-
 +
|Then, &nbsp;<math style="vertical-align: -5px">du=\cos(x)dx.</math>
 +
|-
 +
|Also, we need to change the bounds of integration.
 +
|-
 +
|Plugging in our values into the equation &nbsp;<math style="vertical-align: -5px">u=\sin(x),</math>&nbsp; we get  
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -15px">u_1=\sin\bigg(\frac{\pi}{4}\bigg)=\frac{\sqrt{2}}{2}</math>&nbsp; and &nbsp;<math style="vertical-align: -16px">u_2=\sin\bigg(\frac{\pi}{2}\bigg)=1.</math>&nbsp;
 
|-
 
|-
 
|Therefore, the integral becomes  
 
|Therefore, the integral becomes  
 
|-
 
|-
|
+
|&nbsp; &nbsp; &nbsp; &nbsp; <math style="vertical-align: -19px">\int_{\frac{\sqrt{2}}{2}}^1 \frac{1}{u^2}~du.</math>
::<math style="vertical-align: -19px">\int_{\frac{\sqrt{2}}{2}}^1 \frac{1}{u^2}~du.</math>
 
 
|}
 
|}
  
Line 70: Line 87:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|We now have:
+
|We now have
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp; <math>\begin{array}{rcl}
 
\displaystyle{\int _{\frac{\pi}{4}}^{\frac{\pi}{2}} \frac{\cos(x)}{\sin^2(x)}~dx} & = & \displaystyle{\int_{\frac{\sqrt{2}}{2}}^1 \frac{1}{u^2}~du}\\
 
\displaystyle{\int _{\frac{\pi}{4}}^{\frac{\pi}{2}} \frac{\cos(x)}{\sin^2(x)}~dx} & = & \displaystyle{\int_{\frac{\sqrt{2}}{2}}^1 \frac{1}{u^2}~du}\\
 
&&\\
 
&&\\
Line 80: Line 97:
 
& = & \displaystyle{-\frac{1}{1}-\frac{-1}{\frac{\sqrt{2}}{2}}}\\
 
& = & \displaystyle{-\frac{1}{1}-\frac{-1}{\frac{\sqrt{2}}{2}}}\\
 
&&\\
 
&&\\
& = & \displaystyle{-1+\sqrt{2}.}\\
+
& = & \displaystyle{-1+\sqrt{2}.}
 
\end{array}</math>
 
\end{array}</math>
 
|}
 
|}
 +
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;  
 
!Final Answer: &nbsp;  
 
|-
 
|-
|&nbsp;&nbsp; '''(a)''' &nbsp; <math>\frac{2}{9}(1+x^3)^{\frac{3}{2}}+C</math>
+
|&nbsp; &nbsp; '''(a)''' &nbsp; &nbsp; <math>\frac{2}{9}(1+x^3)^{\frac{3}{2}}+C</math>
 
|-
 
|-
|&nbsp;&nbsp; '''(b)''' &nbsp; <math>-1+\sqrt{2}</math>
+
|&nbsp; &nbsp; '''(b)''' &nbsp; &nbsp; <math>-1+\sqrt{2}</math>
 
|}
 
|}
 
[[009B_Sample_Midterm_1|'''<u>Return to Sample Exam</u>''']]
 
[[009B_Sample_Midterm_1|'''<u>Return to Sample Exam</u>''']]

Revision as of 10:59, 9 April 2017

Evaluate the indefinite and definite integrals.

(a)  

(b)  


Foundations:  
How would you integrate  

        You can use  -substitution.

        Let  
        Then,  

        Thus,

       


Solution:

(a)

Step 1:  
We use  -substitution.
Let  
Then,    and  
Therefore, the integral becomes
       
Step 2:  
We now have
       

(b)

Step 1:  
We use  -substitution.
Let  
Then,  
Also, we need to change the bounds of integration.
Plugging in our values into the equation    we get
         and   
Therefore, the integral becomes
       
Step 2:  
We now have

       


Final Answer:  
    (a)    
    (b)    

Return to Sample Exam